Draft Annual Plan 2005-2006 Maharashtra State Part I - Planning Commission (Planning Commission, 2005)
Government of India has introduced a new initiative in the form of Prime Minister's Gramodaya Yojana (PMGY) in order to achieve the objective of sustainable human development at the village level. The PMGY envisages allocations of Additional Central Assistance to States and UTs for selected basic minimum services in order to focus on certain priority areas of the Government. The allocation for PMGY is sanctioned for two parts viz.
Planning Department, Government of Maharashtra